Characterization and optimization of cellulase production by aspergillus terreus using oil palm empty fruit bunch fibre in submerged culture - Shahriarinour, Mahdi (2011)
The production of three major components of cellulase (FPase, CMCase and B- glucosidase) by Aspergillus terreus was studied in a shake flask experiment. The effects of physical, chemical and biological treatments on the oil palm empty fruit bunch (OPEFB) fibre for subsequent use as substrate for cellulase production were investigated. On the other hand, the effect on the surface morphology of the fibres, were examined under Scanning Electron Microscopy. The effects of different types and concentrations of nitrogen sources on cellulase production were also examined. The optimized medium composition obtained from the shake flask experiment was used for cellulase production in a 2L stirred tank fermenter where the effect of different levels of dissolved oxygen tension (DOT) at a fixed agitation speed on cellulase production was investigated. The experimental data obtained from batch fermentations in a shake flask and the fermenter using the optimized medium were analysed to form the basis for a kinetic model of the process. The effect of different methods of treatment of OPEFB fibre on the rate and degree of hydrolysis was investigated. The use grinded OPEFB fibre increased cellulase production about two fold compared to 10-mm fibre. Chemical treatment with 0.5 % phosphoric acid significantly increased the cellulose and reduced the lignin contents. Cellulase activities, obtained from fermentation using OPEFB fibre treated with phosphoric acid followed by autoclaving at 160°C for 10 min and then treated biologically using effective microorganisms were about three times higher than those obtained in fermentation using untreated OPEFB fibre. The cellulase of A. terreus contained a high proportion of B-glucosidase with the ratio of specific activity of B- glucosidase to FPase of about 8. Yeast extract gave the highest cellulase production followed by peptone, urea and (NH4)2S04. A good agreement between the calculated data and the experimental data for both cell growth and cellulase production were observed, suggesting that the proposed model based on logistic and Luedeking-Piret equations is sufficient to describe the growth of A. terreus and cellulase production. The maximum activities of FPase, CMCase and B-glucosidase obtained from fermentation with 55 % DOT were 2.33, 51.1 and 16.18 U/mL, respectively. Cellulase production in stirred tank fermenter were significantly higher than that obtained in shake flask. The characterization of the proteins purified was shown that eight of the components were known; four endoglucanases (Endo I, II, III and IV), three exoglucanases (Exo I, II and III) and B-glucosidase were isolated from a cellulase preparation derived from A. terreus.